Determination of dimetridazole using carbon paste electrode modified with aluminum doped surface molecularly imprinted siloxane. (10th March 2015) - Hu, Canhui; Deng, Jian; Xiao, Xilin; Zhan, Xiaozhu; Huang, Kaihui; Xiao, Ni; Ju, Saiqin
Graphical abstract: Highlights: A novel surface molecularly imprinted siloxane modified CPE for DMZ detection. Al doping introduced extra Lewis acid-base interaction between imprinted sites and DMZ. DPSV for quantification of DMZ in food and feed samples at trace level. The sensor showed high sensitivity, good selectivity and acceptable precision. Abstract: For the first time, a simple and highly sensitive electrochemical dimetridazole (DMZ) sensor based on a carbon paste electrode modified with core-shell aluminum doped surface molecularly imprinted siloxane has been developed and tested. Because of aluminum doping, the surface imprinting sensor exhibits higher rebinding capacity, recognition ability and affinity for DMZ in comparison with the aluminum free and the non-imprinted ones. In addition, the as-prepared sensor shows good stability and satisfactory reproducibility for the determination of DMZ. Under optimal experimental conditions, the peak currents by differential pulse stripping voltammetry were found to vary linearly with DMZ concentrations in the range from 1.0 × 10 −8 to 1.0 × 10 −6 mol L −1 and 1.0 × 10 −6 to 1.0 × 10 −4 mol L −1, with a detection limit of 3.6 × 10 −9 mol L −1 . This sensor was successfully employed to detect DMZ in egg, milk powder, and pig feed samples with acceptable recoveries of 91.4% to 107.6%, which was verified by high performance liquid chromatography.